INFLUENCE CRYSTALLOGRAPHIC ORIENTATION OF MINERALS ON THE ELASTIC PARAMETERS AND ACOUSTIC ANISOTROPY OF BIOTITE SCHISTS KRYVORIZHZHYA - Bezrodny, D. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Influence of tectonic deformations on acoustic and elastic anisotropy parameters of Krivbass biotite schists is studied. Mathematical modeling using a multicomponent model of the geological environment is conducted.